Search for prompt production of pentaquarks in charm hadron final states - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Cocha Toapaxi, Carlos; De Cian, Michel; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; Langenbruch, Christoph; Leverington, Blake; Marks, Jörg; et al. (Physical review, 2024)
A search for hidden-charm pentaquark states decaying to a range of Σ𝑐⁢¯𝐷 and Λ+𝑐⁢¯𝐷 final states, as well as doubly charmed pentaquark states to Σ𝑐⁢𝐷 and Λ+𝑐⁢𝐷, is made using samples of proton-proton collision data corresponding to an integrated luminosity of 5.7 fb−1 recorded by the LHCb detector at √𝑠 =13 TeV. Since no significant signals are found, upper limits are set on the pentaquark yields relative to that of the Λ+𝑐 baryon in the Λ+𝑐 →𝑝⁢𝐾−⁢𝜋+ decay mode. The known pentaquark states are also investigated, and their signal yields are found to be consistent with zero in all cases.